The Influence of Hierarchical Masks on Masked Repetition Priming: Evidence From Event-Related Potential Investigation - Mei, Ying; Dai, Yuqian; Lei, Yi (Frontiers in Human Neuroscience, 2019)
The discussion about relationship between prime and target has contribute to the mechanism of priming effect and object recognition. Nevertheless, the role of relationship between mask and target in those cognitive processes remains unquestioned. In the present study, we aim to investigate how mask-target hierarchical relationship may affect word priming and familiarity, by using the masked repetition paradigm and manipulating three hierarchical relationship between mask and target. It is hypothesized that a closer hierarchical relationship between mask and target is associated with a higher mask target similarity, and thereby it leads to a worse recognition performance. Our behavioral results do not support this hypothesis by showing no effect of mask target hierarchical relationship on response time and accuracy. ERPs indicated that highly similar mask-target triggered(i.e., the subordinate-subordinate-subordinate trials) larger N1 amplitudes, suggesting that it require more cognitive resource to discriminate the stimuli. In addition trials with highly similar mask-target hierarchical relationship induced smaller P2 (150-250 ms) and larger mid-frontal FN400 amplitudes than do trials with low mask target similarity(i.e., the subordinate-basic-subordinate and the subordinate-superordinate-subordinate trials). Our results suggested that the similarity between mask and target may impede conceptual fluency to reduce word priming and familiarity effect.